KAJIAN PEMANFAATAN TANDAN KOSONG KELAPA SAWIT (TANKOS) SEBAGAI KATALIS BASA PADA REAKSI TRANSESTERIFIKASI METIL ESTER - Asep Ruchiyat (POLITEKNIK NEGERI BENGKALIS, 2018)
The energy and fuel crisis has occurred since the late1970s. Therefore, in the early 1980, it was assumed that the fuel reserves of the non-renewable sources (petroleum-based fuels) could possibly run out and new alternative sources should be found out. Biodiesel is one alternative renewable and biodegradable energy source that is more eco-friendly compared to petroleum diesel. Statistically, based on the Anava test, the result is 5%. It is proved that the addition of concentrated ash from palm oil waste and the temperature of transesterification reaction significantly effects kinematic viscosity at 25 °C (cp), acid number (mg/gr), and sedimentary water content (%). Meanwhile, mass parameter (gr/cm3) statistically has no significant effect. The quality of methyl esters that is produces especially the parameter of acid has fulfilled the standard quality requirement of biodiesel according to SNI-04-7182-2006 althoughwater content parameter, viscosity or mass has not fulfilled SNI quality standard.